Research on the impact of digital transformation on green development of manufacturing enterprises - Chen, Shi; Yang, Yang; Wu, Tingting (Frontiers in Energy Research, 2023)
Digital development is changing with each passing day, and the traditional manufacturing industry is gradually shifting from extensive development to intensive development, the most prominent manifestation of which is the digital transformation and development of enterprises. This paper first discusses the internal mechanism of digital transformation promoting the green development of manufacturing enterprises from three aspects: product greening, technology greening and investment greening. Then, based on the panel data of China’s listed manufacturing enterprises from 2011 to 2019, the fixed effect model, two-stage least squares method, mediating effect model and moderating effect model were used to test the relationship between them. The results show that digital transformation can promote the green development of manufacturing enterprises, and this conclusion still holds after a series of robustness tests. The empirical results of the mediating effect model show that digital transformation promotes the green development of manufacturing enterprises through three mediating paths: increasing green product output, technological innovation level and green investment level. Moreover, the promoting effect of digital transformation on the green development of enterprises will be moderated by the heterogeneous effect of environmental uncertainty. Therefore, accelerating the digital development of enterprises and promoting the construction of digital China is conducive to the green development of enterprises, and finally realizing the common development of digitalization and greening.